EFFECTS OF SMOKING - Periasamy, Yashila; Dinesh.S.P, Saravana; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2019)
It is well known that smoking contributes to the development of lung cancer and cardiovascular disease, and there is weighty evidence that it has a considerable influence on oral health. Smoking has many negative effects on the mouth, including staining of teeth and dental restorations, reduction of the ability to smell and taste, and the development of oral diseases such as smoker’s palate, smoker’s melanosis,oral candidiasis and dental caries, periodontal disease, implant failure, oral pre cancer and cancer. From a qualitative point of view the latter is obviously the most serious tobacco-related effect in the mouth. Quantitatively, however, importance has been attached to periodontitis, which affects a large proportion of the population, and during recent years more attention has been given to implant survival rates. As tobacco accounts for such a high proportion of these diseases, comprehensive tobacco control policies are required to make progress in reducing the burden of tobacco-related oral diseases.The present review focuses on smoking‐associated oral health problems in older adults, and the steps required for cessation of the habit. Effective treatments to prevent tobacco use and increase cessation are available and need greater implementation. Dental practices may provide a uniquely effective setting for tobacco prevention and cessation.